2021
DOI: 10.1177/0972262921992152
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leverages and Operating Efficiency on Market Value Added: Empirical Evidence from India

Abstract: This article examines the relationship between the market value added and degree financial leverage, degree of operating leverage, and asset turnover ratio of the listed firms in India. The period of study was from 2013 to 2019, and data were collected in annual frequency. Our study concludes that the degree of financial leverage and asset turnover ratio are significantly and negatively associated with the market value added of listed firms in India. We also reported an insignificant relationship between marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…On the other hand, there are some drawbacks of these restrictions and have influenced with more efficient and significant measurements (Sura, Panchal, & Lather, 2023). EVA is considered as a better criterion than traditional measurements such as ROA, ROE, and ROI to measure value creation and internal performance of companies (Kumar, Bhatia, & Chattopadhyay, 2022). increase in share value, but in fact there is no evidence that financial markets recognize and include EVA in their share prices (Shubita, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, there are some drawbacks of these restrictions and have influenced with more efficient and significant measurements (Sura, Panchal, & Lather, 2023). EVA is considered as a better criterion than traditional measurements such as ROA, ROE, and ROI to measure value creation and internal performance of companies (Kumar, Bhatia, & Chattopadhyay, 2022). increase in share value, but in fact there is no evidence that financial markets recognize and include EVA in their share prices (Shubita, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a literature review and based on previous research, the influence between EVA and financial ratios to MVA varies. Several studies have found a positive effect between EVA and MVA (Faiteh & Aasri, 2023) (Kumar, Bhatia, & Chattopadhyay, 2022) (Supriani & Pernamasari, 2021) (Nakhaei & Hamid, 2013) which means it is expected that when the company conducts M&A and there is a positive value on EVA, this provides information that the company's value is increases too, but some find it has no influence (Rahmawati & Yunita, 2018). Lacking influence of EVA with market value will make investors cannot use the same internal value creation measures as traditional performance measures (Alipour & Pejman, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Hasil pengujian selanjutnya menunjukkan bahwa asset management memilki pengaruh negatif dan signifikan terhadap firm value dengan koefisien sebesar 11.61 dan nilai signifikansi sebesar 0.0222 < 0.05. Hasil ini bertentangan dengan penelitian dariKumar et al (2021); Miswanto & Oematan (2020);Akinleye & Olufemi (2019). Berdasarkan observasi dari sampel perusahaan penelitian, besar kemungkinan terjadinya hubungan yang negatif antara perputaran asset dengan firm value dikarenakan perputaran asset yang sudah sedemikian produktif dan optimal dalam menghasilkan penjualan mengalami kendala dalam menghasilkan kas dalam periode yang cepat.…”
unclassified